Advanced Three-Dimensional Technologies in Craniofacial Reconstruction. Issue 1 (July 2021) - Day, Kristopher M.; Kelley, Patrick K.; Harshbarger, Raymond J.; Dorafshar, Amir H.; Kumar, Anand R.; Steinbacher, Derek M.; Patel, Pravin; Combs, Patrick D.; Levine, Jamie P.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Describe the evolution of three-dimensional computer-aided reconstruction and its current applications in craniofacial surgery. 2. Recapitulate virtual surgical planning, or computer-assisted surgical simulation, workflow in craniofacial surgery. 3. Summarize the principles of computer-aided design techniques, such as mirror-imaging and postoperative verification of results. 4. Report the capabilities of computer-aided manufacturing, such as rapid prototyping of three-dimensional models and patient-specific custom implants. 5. Evaluate the advantages and disadvantages of using three-dimensional technology in craniofacial surgery. 6. Critique evidence on advanced three-dimensional technology in craniofacial surgery and identify opportunities for future investigation. Summary: Increasingly used in craniofacial surgery, virtual surgical planning is applied to analyze and simulate surgical interventions. Computer-aided design and manufacturing generates models, cutting guides, and custom implants for use in craniofacial surgery. Three-dimensional computer-aided reconstruction may improve results, increase safety, enhance efficiency, augment surgical education, and aid surgeons' ability to execute complex craniofacial operations. Subtopics include image analysis, surgical planning, virtual simulation, custom guides, model or implant generation, and verification of results. Clinical settings for the use of modern three-dimensional technologies include acquired and congenital conditions in both the acute and the elective settings. The aim of these techniques is to achieve superior functional and aesthetic outcomes compared to conventional surgery. Surgeons should understand this evolving technology, its indications, limitations, and future direction to use it optimally for patient care. This article summarizes advanced three-dimensional techniques in craniofacial surgery with cases highlighting clinical concepts.